The push and pull factors of China’s outward foreign direct investment in BRI countries - Lee, Sin Yee; Karim, Zulkefly Abdul; Khalid, Norlin; Zaidi, Mohd Azlan Shah (Technological and Economic Development of Economy, 2022)
The purpose of this study is to examine the role of push and pull factors that have influenced China’s outward foreign direct investment (COFDI) in the Belt and Road Initiative (BRI) countries. The sample of BRI countries is divided according to three geographical regions representing Europe, MENA, and Asia for better understanding of the main factors that influence the COFDI across the respective regions. This study supports Dunning’s FDI theory in modeling the determinants of COFDI in BRI economies by focusing on the role of push and pull factors. This present study also extends and improves the existing research by considering the new factors, new methodology, and splitting the sample BRI economies. Thus, a static, dynamic panel and quantile regression technique was employed to model COFDI determinants for 50 BRI countries from 2005 to 2016. The main findings revealed that China’s minimum wage policy, including the host countries’ natural resources, labor cost, and institutional factors were the key determinants influencing COFDI. However, some determinants such as the host countries’ gross domestic product, total patents, trade openness, and inflation rate did not significantly influence COFDI. By splitting the sample according to the respective regions, the results revealed that only the minimum wage policy significantly influenced COFDI in the European region. In comparison, natural resources, gross domestic product, and minimum wage policy were statistically significant for the MENA region. In the Asian region, minimum wage policy, government index, and trade openness were proven essential for COFDI. The policy implications from this study suggest that MNCs from China need to strategize their location for investment in BRI economies. In complement, the BRI recipient countries need to show their advantage and strength in attracting more FDI from China. BRI economies and China MNCs can also be leveraged through understanding how strong the push and pull factors are exerting on outward investment from China.First published online 30 March 2022